2021
DOI: 10.1002/anie.202109735
|View full text |Cite
|
Sign up to set email alerts
|

Feedback and Communication in Active Hydrogel Spheres with pH Fronts: Facile Approaches to Grow Soft Hydrogel Structures

Abstract: Compartmentalized reaction networks regulating signal processing, communication and pattern formation are central to living systems. Towards achieving life‐like materials, we compartmentalized urea‐urease and more complex urea‐urease/ester‐esterase pH‐feedback reaction networks into hydrogel spheres and investigate how fuel‐driven pH fronts can be sent out from these spheres and regulated by internal reaction networks. Membrane characteristics are installed by covering urease spheres with responsive hydrogel s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 70 publications
0
38
0
2
Order By: Relevance
“…For example, our group and others have been developing relatively mature out-of-equilibrium chemical and enzymatic reactions networks. 599,600,609,618–624 610 But, currently these systems are mostly applied to the self-assembly of small molecules and entities. A further coupling to the colloidal domain would tremendously broaden and enrich the structures and properties of colloidal chains in out-of-equilibrium state.…”
Section: Synthetic Strategies For 1d Chainsmentioning
confidence: 99%
“…For example, our group and others have been developing relatively mature out-of-equilibrium chemical and enzymatic reactions networks. 599,600,609,618–624 610 But, currently these systems are mostly applied to the self-assembly of small molecules and entities. A further coupling to the colloidal domain would tremendously broaden and enrich the structures and properties of colloidal chains in out-of-equilibrium state.…”
Section: Synthetic Strategies For 1d Chainsmentioning
confidence: 99%
“…To demonstrate this, the TBA cycle is coupled to the urea/urease enzymatic reaction. [24,31] Urease is useful to couple to in this context, as it converts urea to ammonia and carbon dioxide, therefore leading to a rise in pH. As a device, we incorporated a cylindrical patch (h = 4 mm, r = 3.5 mm) composed of 25 wt% PEGDA6K containing 10 mg•mL -1 urease atop an A 3 /AMPS bilayer like those shown in Figure 3.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, we have recently shown how pH-feedback systems based on CRNs of acid-and baseproducing enzymatic and non-enzymatic systems can be precisely controlled in their transient lifetime and pH amplitude. [23][24] We showed that such pH-feedback systems can be coupled to program transient self-assemblies, [25] molecular machines, [26][27][28] DNA devices, [29] hydrogelation [23,[30][31] or photonics [32] with precise lifetimes. Two aspects are important when aiming to instruct soft robotic device with autonomous motion by CRNs.…”
Section: Introductionmentioning
confidence: 99%
“…175 Over the last decade, the quest for accessing such dynamic catalytic structures that are transiently formed in the presence of chemical fuels has gained significant interest in the emerging field of systems chemistry. 50,51,[176][177][178][179][180][181][182] From the perspective of this review, we have included selected examples where transient self-assembly has been achieved utilizing enzyme like activity from assembled states of simple building blocks. These examples specifically utilize augmented catalytic performance from the self-assembled state to access transient self-assemblies under non-equilibrium conditions.…”
Section: Catalytic Assemblies Under Nonequilibrium Conditionsmentioning
confidence: 99%